Measuring cognitive levels in high-stakes testing: A CDM analysis of a university entrance examination using Bloom’s Taxonomy - Ravand, Hamdollah; Shahi, Reza; Effatpanah, Farshad; Moghadamzadeh, Ali (Frontiers in Education, 2025)
The aim of this study was twofold. First, this study explored the potential use of a high-stakes multiple-choice test for measuring cognitive complexity by using Bloom’s Taxonomy and applying cognitive diagnostic models. Second, it investigated the interplay of cognitive complexity with gender and item difficulty. Data from 1,000 applicants to English PhD programs were analyzed. Six experts coded test items based on the cognitive levels they target. Q-matrices were constructed, one for each expert, specifying item-cognition relationships. The G-DINA model was used to assess these relationships. Based on the best-fitting Q-matrix, 27% of the items measured the lowest cognitive level (Remember), 50% measured Understand, and 23% measured Analyze levels. Test takers demonstrated mastery of these levels by 56, 39, and 28%, respectively. Findings indicated that the test primarily assessed lower levels of Bloom’s Taxonomy. In addition, the results showed that male test takers outperformed female counterparts at higher levels. Furthermore, the analysis showed that cognitive complexity contributed to item difficulty. Finally, implications were discussed, and suggestions were made.